Experimental investigation of photovoltaic modules cooling system - Farhana, Z.; Mohd Irwan, Yusoff; Azimmi, R. M. N.; Nurul Razliana, Abd Razak; Gomesh Nair, Shasidharan (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org